2021
DOI: 10.1016/j.epsl.2021.117064
|View full text |Cite
|
Sign up to set email alerts
|

Late Carboniferous paleoelevation of the Variscan Belt of Western Europe

Abstract: We present the first stable isotope paleoaltimetry estimates for the hinterland of the eroded Variscan Belt of Western Europe based on the hydrogen isotope ratios of muscovite from syntectonic leucogranites that have been emplaced at ∼ 315 Ma. We focus on the Limousin region (Western Massif Central, France) where peraluminous granites are spatially associated with strike-slip and detachment shear zones that developed as a consequence of Late Carboniferous syn-to post-orogenic extension. In this region, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Late Carboniferous elevation of ~3 km estimated for the Variscan belt (Massif Central) (Dusséaux et al, 2021) and evidence of the lack of marked rain shadow that suggests moderate elevation of 2000 m during late Carboniferous-Permian (Roscher and Schneider, 2006) supports this model. We have estimated that the mantle heat flow established during the Late Carboniferous-Permian (300-270 Ma) was maintained to high values of 32 mW/m 2 (Figure 9).…”
Section: Paleogene Kinematic Reorganisation: Increasing Role Of North Atlanticmentioning
confidence: 61%
“…Late Carboniferous elevation of ~3 km estimated for the Variscan belt (Massif Central) (Dusséaux et al, 2021) and evidence of the lack of marked rain shadow that suggests moderate elevation of 2000 m during late Carboniferous-Permian (Roscher and Schneider, 2006) supports this model. We have estimated that the mantle heat flow established during the Late Carboniferous-Permian (300-270 Ma) was maintained to high values of 32 mW/m 2 (Figure 9).…”
Section: Paleogene Kinematic Reorganisation: Increasing Role Of North Atlanticmentioning
confidence: 61%
“…These data indicate that meteoric water can infiltrate to 8-10 km from the surface, suggesting that they can flow downward and laterally along the STDS, and then mixed with deeply derived fluids. Previous studies have demonstrated that meteoric water can reach the brittle-ductile transition in the crust through faults or detachment shear zones, such as in the Cordilleran metamorphic core complexes (e.g., Fricke et al, 1992;Kerrich, 1988;Mulch, Teyssier, Cosca, & Vennemann, 2006;Wickham & Taylor, 1985), Variscan Shear Zone (Dusséaux et al, 2019(Dusséaux et al, , 2021Lemarchand et al, 2012), STDS (Gébelin et al, 2013(Gébelin et al, , 2017, Alpine Fault (Menzies et al, 2014), and Menderes metamorphic core complex (Hetzel et al, 2013). These previous studies have documented surface-derived fluids flowing down and mixing with deeply derived fluids (Gébelin, Teyssier, Heizler, & Mulch, 2015;Gottardi, Kao, Saar, & Teyssier, 2013;Person, Mulch, Teyssier, & Gao, 2007).…”
Section: The Infiltration Depth Of Meteoric Fluidsmentioning
confidence: 98%
“…Fluids from different sources have distinct isotopic signatures (Yardley & Bottrell, 1992). A relatively low hydrogen (δ 2 H) and oxygen (δ 18 O) isotopic composition of fluid can be indicative of a meteoric component (e.g., Zang et al, 2019), and thus used as a palaeoaltimeter (e.g., Campani, Mulch, Kempf, Schlunegger, & Mancktelow, 2012;Dusséaux, Gébelin, Ruffet, & Mulch, 2021;Gébelin et al, 2013;Gébelin, Mulch, Teyssier, Page Chamberlain, & Heizler, 2012;Mulch & Chamberlain, 2007;Rowley & Garzione, 2007). Low δ 2 H and δ 18 O ratios recorded in extensional detachment systems indicate that meteoric fluids can circulate into different depths and even into ductile detachment zones (e.g., Gottardi et al, 2015;Morrison & Anderson, 1998).…”
mentioning
confidence: 99%
“…Assessing the source of fluids in such hydrothermal systems has a range of applications including constraining the conditions for mineralization and ore deposition (Ballouard et al, 2017(Ballouard et al, , 2018aBeaudoin et al, 1991;Boiron et al, 2003) or paleoaltimetry reconstructions if surface-derived (meteoric) fluids are present (e.g. Dusséaux et al, 2021;Gébelin et al, 2012Gébelin et al, , 2013Grambling et al, 2022;Mulch et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gébelin et al, 2017Gébelin et al, , 2013, and in the Variscan belt of Western Europe (e.g. Ballouard et al, 2018aBallouard et al, , 2017Ballouard et al, , 2015Dusséaux et al, 2021Dusséaux et al, , 2019. Some of these studies (e.g.…”
Section: Introductionmentioning
confidence: 99%